Improved PID Control Design for Electric Power Steering DC Motor - A. Turan (IEEE Access)
As technology continues to evolve, the hydraulic power steering system (HPS) used for steering control in vehicles had begun to be changed by the electric power steering (EPS) system, which offers the advantage of better controllability. This study aims to achieve more precise and stable control of a modeled EPS motor using an innovative control method. The effects of a PID control designed with a new approach, on the system were investigated to compare it with the Ziegler Nichols, Internal Model Control (IMC), Tyreus Luyben, and Haugen methods mentioned in the study. The foundation of the presented design technique is based on calculating the optimal proportional gain ( $k_{p}$ ) value to minimize the error rates of the settling time ( $t_{s}$ ) and maximum overshoot ( $M_{p}$ ) in a stable loop, and then deriving the other PID controller parameters. This process was achieved by iterative tuning within the stable region of the control loop and calculating the optimum controller parameters. Reducing the calculation complexity of PID control parameters and improving their adaptability are also among the desired goals with the proposed method. According to the results, it was stated that the PID controller calculated with the new approach had better $M_{p}$ , $t_{s}$ , and rise time ( $t_{r}$ ) performance values compared to other controllers compared to the ones with which it was compared, and that no steady state error (SSE) was obtained.